Pengaruh Asset Tangibility, Effective Tax Rate dan Non Debt Tax Shield Terhadap Struktur Modal - Afridayani, Afridayani (Akuisisi : Jurnal Akuntansi, 2023)
Asset Tangibility, Effective Tax Rate and Non-Debt Tax Shield affect the capital structure. This study aims to examine the effect of asset tangibility, effective tax rate and non-debt tax shield. This type of research is associative research and this research is quantitative. The population of the study was 26. Sampling was carried out by purposive sampling and obtained 18 manufacturing companies in the food and beverage sub-sector that were listed on the IDX according to the criteria. The data in this study were analyzed using the classical assumption test, the R determinant test and the t-test were carried out with the help of Eviews 9 software. The results showed that simultaneously Asset Tangibility, Effective Tax Rate and Non-Debt Tax Shield were able to influence capital structure. The results of the study partially show that the Asset Tangibility and Effective Tax Rate variables partially have a positive effect on capital structure and the Non-debt tax shield variable partially has no effect on capital structure.